Nematofauna of three species of lizards (Sauria: Tropiduridae and Gekkonidae) from National Reserve Paracas, Ica, Peru - Pérez Z., José (2007)
The nematode Thubunaea iguanae and Spauligodon viracochai are reported for three species of Spauligodon viracochai are reported for three species of Spauligodon viracochai lizards from Paracas National Reserve, Ica, Peru. The fi rst nematode was found on Microlophus peruvianus and peruvianus and peruvianus Microlophus thoracicus thoracicus while Microlophus thoracicus thoracicus while Microlophus thoracicus thoracicus the second one was found on Phyllodac- tylus angustidigitus . Reports are two new host records and a new locality record for T. iguanae, and a fi rst record for South America, and a new host for S. viracochai .